2019
DOI: 10.1128/aac.02366-18
|View full text |Cite
|
Sign up to set email alerts
|

Role of TEM-1 β-Lactamase in the Predominance of Ampicillin-Sulbactam-Nonsusceptible Escherichia coli in Japan

Abstract: We investigated the epidemiology and resistance mechanisms of ampicillin-sulbactam-nonsusceptible Escherichia coli, focusing on the role of the TEM-1 β-lactamase. We collected all nonduplicate E. coli clinical isolates at 10 Japanese hospitals during December 2014 and examined their antimicrobial susceptibility, β-lactamases, TEM-1 transferability, TEM-1 β-lactamase activity, outer membrane protein profile, membrane permeability, and clonal genotypes. Among the 329 isolates collected, 95 were ampicillin-sulbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…It is reported that the gene mutation-induced single amino acid substitutions at Ambler positions Met 69 , Ser 130 , Arg 244 , Arg 275 , and Asp 276 in TEM and SHV β-lactamases may result in enzymes with reduced affinity for β-lactamase inhibitors ( Ramdani-Bouguessa et al 2011 ; Winkler et al 2015 ). Another possible mechanism is that resistance to BL/BLIs may result from gene amplification, and subsequent hyperproduction of β-lactamase ( Sun et al 2013 ; Noguchi et al 2019 ; Zhou et al 2019 ; Hubbard et al 2020 ). Mutations in the promoters have been shown to be responsible for bla OXY-1 and bla SHV-1 amplification ( Fournier et al 1999 ; Han et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the gene mutation-induced single amino acid substitutions at Ambler positions Met 69 , Ser 130 , Arg 244 , Arg 275 , and Asp 276 in TEM and SHV β-lactamases may result in enzymes with reduced affinity for β-lactamase inhibitors ( Ramdani-Bouguessa et al 2011 ; Winkler et al 2015 ). Another possible mechanism is that resistance to BL/BLIs may result from gene amplification, and subsequent hyperproduction of β-lactamase ( Sun et al 2013 ; Noguchi et al 2019 ; Zhou et al 2019 ; Hubbard et al 2020 ). Mutations in the promoters have been shown to be responsible for bla OXY-1 and bla SHV-1 amplification ( Fournier et al 1999 ; Han et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…34 Particularly, ST131 is an E. coli strain responsible for a worldwide pandemic and it carries a broad range of pathogenicity and ARGs, including a variety of β-lactamase genes on a transferable plasmid. [35][36][37] In Japan, it has been reported that 92.9% of EPOs are bla CTX-M gene positive. 38 The CTX-M genes (bla CTX-M-14 , bla CTX-M-15 , bla CTX-M-27 and bla CTX-M-2 , listed in descending order of size) 39 have been identified in Japan as well, and gene sequences obtained in this study are similar to that (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…6). ST131 is an E. coli isolate responsible for a worldwide pandemic and carries a broad range of pathogenicity and antimicrobial resistance-associated genes, including a variety of βlactamase genes (CTX-M family, TEM, SHV, and CMY β-lactamases) on a transferable plasmid [74][75][76][77].…”
Section: Genome Comparison Between Sewage and Clinical Isolatesmentioning
confidence: 99%